2018
DOI: 10.33451/florafauna.v24i1pp91-96
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Certain Green Gram, Vigna Radiata Genotypes Against Sucking Insect Pests

Abstract: The twenty genotypes of green gram namely Pant M4, ML 2410 , VGG 15-030, KM 2349, ML 818, Pusa 1671, Pusa 1672, Pant M6, PM 11-26, SML 1811, COGG 912, RMG 1092, PM 11-25, AKM 12-24, IGKM 06.26.5, RMG 1087, VGG 10-008, IGKM 05- 18-2, AKM 12-14, HUM-12 were raised under natural condition to study the population build-up of major sucking insect pests viz., Bemisia tabaci, Empoasca kerri, Caliothrips indicus on green gram. The results of present investigation revealed that maximum population of B. tabaci w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This theory, however, was refuted by Wallis et al (1981), Turnbull (1986), Upadhyaya et al (2007), Saxena et al (2021) who demonstrated that in comparison to late types, the earlier flowering pigeonpea genotypes were relatively photo-insensitive. Akinola and Whiteman (1974), Sharma et al (1981), Singh and Saxena (1981) and Saxena and Sharma (1990) reported that the time taken from sowing to flowering was highest in the sowings made prior to the longest day; and it reduces progressively as the sowings are delayed into the shortening days. Recently, Saxena et al (2021) reported that the flowering time and photosensitivity in pigeonpea shared a strong positive relationship.…”
Section: Daylength Sensitivity For Flowering Time In Pigeonpea-a Brie...mentioning
confidence: 99%
“…This theory, however, was refuted by Wallis et al (1981), Turnbull (1986), Upadhyaya et al (2007), Saxena et al (2021) who demonstrated that in comparison to late types, the earlier flowering pigeonpea genotypes were relatively photo-insensitive. Akinola and Whiteman (1974), Sharma et al (1981), Singh and Saxena (1981) and Saxena and Sharma (1990) reported that the time taken from sowing to flowering was highest in the sowings made prior to the longest day; and it reduces progressively as the sowings are delayed into the shortening days. Recently, Saxena et al (2021) reported that the flowering time and photosensitivity in pigeonpea shared a strong positive relationship.…”
Section: Daylength Sensitivity For Flowering Time In Pigeonpea-a Brie...mentioning
confidence: 99%
“…The annual yield loss due the insect-pests is estimated to be 30 per cent in mung bean and urd bean. On an average, 2.5 to 3.0 million tonnes of pulses are lost annually due to insect-pest problems (Rabindra et al, 2004).Thrips (Megalurothrips distalis Karny), jassids (Empoasca kerri Pruthi) whiteflies (Bemisia tabaci Gennadius), gram pod borer (Helicoverpa armigera Hubner) and spotted pod borer (Maruca vitrata Fabricius) are major insect-pest causing considerable yield loss in green gram (Singh et al, 2016;Mahalakshmi et al, 2018).…”
Section: Declarationmentioning
confidence: 99%
“…The major pulse crops that have been domesticated and are under cultivation include black gram, chickpea, cowpea, faba bean, grass pea, mungbean, horse gram, lablab bean, lentil, moth bean, pea and pigeon pea. Mungbean is the third most important pulse crop of India after chickpea and pigeonpea [2]. Green gram in the cereal cropping system has the potential to increase farm income, improve human health and soil fertility as well as to promote long term sustainability of agriculture [3].…”
Section: Introductionmentioning
confidence: 99%
“…Green gram in the cereal cropping system has the potential to increase farm income, improve human health and soil fertility as well as to promote long term sustainability of agriculture [3]. The nutritive value of mungbean is high and easily digestible protein with approximately protein 25-28%, oil 1.0-1.5%, fibre 3.5-4.5%, ash 4.5-5.5%, carbohydrate 62-65%, water 9.1%, and vitamins on dry weight basis [2]. Being an important short-duration Kharif grain legume, mungbean is grown extensively in major tropical and subtropical countries of the world [4].…”
Section: Introductionmentioning
confidence: 99%